2014
DOI: 10.1016/j.spinee.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of discectomy on intervertebral disc biology can be decelerated by growth factor treatment during surgery: a large animal organ culture model

Abstract: BACKGROUND CONTEXT Lumbar discectomies are common surgical interventions that treat radiculopathy by removing herniated and loose intervertebral disc (IVD) tissues. However, remaining IVD tissue can continue to degenerate resulting in long-term clinical problems. Little information is available on the effects of discectomy on IVD biology. Currently no treatments exist that can suspend or reverse the degeneration of the remaining IVD. PURPOSE To improve knowledge how discectomy procedures influence IVD physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…TGF-β has been reported to increase proteoglycan production to adjust the proliferation of type II collagen intervertebral disk cells and reduce matrix degradation to thereby regulate the metabolism of intervertebral disc cells (33,34). While certain studies found that proteoglycan production in nucleus pulposus cells was increased through gene therapy with TGF-β, it is inferred that TGF-β is a protective cytokine in the intervertebral disc (35)(36)(37). In the present study, an increasing trend of TGF-β1 at 1 month post-operation was identified, while it had significantly decreased at 3 months.…”
Section: Control Groupcontrasting
confidence: 41%
“…TGF-β has been reported to increase proteoglycan production to adjust the proliferation of type II collagen intervertebral disk cells and reduce matrix degradation to thereby regulate the metabolism of intervertebral disc cells (33,34). While certain studies found that proteoglycan production in nucleus pulposus cells was increased through gene therapy with TGF-β, it is inferred that TGF-β is a protective cytokine in the intervertebral disc (35)(36)(37). In the present study, an increasing trend of TGF-β1 at 1 month post-operation was identified, while it had significantly decreased at 3 months.…”
Section: Control Groupcontrasting
confidence: 41%
“…As a preliminary proof of concept study to assess the potential therapeutic effects of a PAR2 antagonist on MC-induced IVD degeneration, we chose to use a bovine ex vivo organ model which has been utilized previously as a model of IVD degeneration and to screen therapeutics (Purmessur et al, 2013b; Illien-Jünger et al, 2014; Grant et al, 2016). Treatment of IVD organ culture samples with PAR2A had no detectable impact on viability for AF as demonstrated by MTT staining co-localized with DNA stain Hoechst (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Isolated samples were washed in 70% EtOH and PBS before being treated with isolation (Prime Growth 319-511-EL) and neutralizing solution (Prime Growth 319-512-CL) and then culture in Wisent Prime Growth Media (Prime Growth 319-510-CL) + 1% P/S for 24 h at 37°C 5% CO 2 20% O 2 according to Wisent protocol as outlined prior (Grant et al, 2016). Injury was induced for relevant samples via an “X” cut through the AF region and partial NP removal (Illien-Jünger et al, 2014). After 10 days, samples were split into the following groups: (1) control with no injury or treatment, (2) injury+MCCM, or (3) injury+MCCM+100 nM PAR2A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TGF-b1 can upregulate the AFCs proliferation, and have synergic effects with some growth factors on cell proliferation, including insulin-like growth factor-I (IGF-I) and fibroblast growth factor-2 (FGF-2) 80,81 . In rat NPCs, exogenous administration of TGF- Apart from the promotion of cell proliferation, TGF-b signaling can delay IVD degeneration by mitigating cell death in the IVD 76,84 . Apoptosis and autophagy have been confirmed to play a key role in the progression of IVD degeneration 85 .…”
Section: Promotion Of Cell Proliferation and Inhibition Of Cell Deathmentioning
confidence: 99%